The Effect of Planned Instruction on Metacognitive Awareness of Reading Strategies - Nath, Pranjana Kalita (LEARN Journal: Language Education and Acquisition Research Network, 2021)
Metacognition, often used as a component of reading strategy instruction, has two dimensions - knowledge about cognition and regulation of cognition. Though many studies explore the connection between metacognitive strategies and development of reading comprehension abilities, not many examine how the two dimensions of metacognition interact to affect the general metacognitive awareness of reading strategies. This study aims to fill this gap by investigating how planned instruction incorporating knowledge about cognition affects general metacognitive awareness of reading strategies of non-native ESL learners in tertiary education. It reports on the effect of a planned instructional intervention carried out in the first semester of an Academic Reading course. A statistical analysis reveals that such planned instruction results in slightly improved metacognitive awareness of reading strategies, and does not lead to significant change in terms of relative preference of use of individual reading strategies. The study also finds that students with lower level of perceived awareness prior to the instruction benefit more than those with higher level of perceived awareness, and that it helps reduce the gap between students with higher level and those with lower level of awareness, and prepares the group to learn higher order strategies for regulation of cognition.